2018
DOI: 10.12659/msm.909452
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Cell Growth, Drug Resistance, and Epithelial-Mesenchymal Transition Are Suppressed by g-Secretase Inhibitor RO4929097

Abstract: BackgroundThe Notch signaling pathway has been reported to play a pivotal role in tumorigenesis. Emerging evidence has demonstrated that the Notch signaling pathway regulates several cellular processes. The present study investigated the effect of the Notch signaling pathway on cell growth, invasiveness, and drug resistance, as well as epithelial-mesenchymal transition (EMT), of cervical cancer cells.Material/MethodsWe used quantitative real-time polymerase chain reaction (qRT-PCR) and Western blot analysis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Furthermore, the molecular therapeutics targeting key biomarkers such as EGFR receptors showed some success in clinical trials, but the cancer stem cell-derived drug resistance hindered the drug effects [152] . Recently, Shang et al [71] found that Notch signaling is expressed in both CD133+ and CD133-cells. However, the activation of Notch signaling in CD133+ cells leads to a higher proliferation rate and lower apoptosis and results in targeted-therapy resistance, compared to CD133-cells.…”
Section: Notch Signaling and Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the molecular therapeutics targeting key biomarkers such as EGFR receptors showed some success in clinical trials, but the cancer stem cell-derived drug resistance hindered the drug effects [152] . Recently, Shang et al [71] found that Notch signaling is expressed in both CD133+ and CD133-cells. However, the activation of Notch signaling in CD133+ cells leads to a higher proliferation rate and lower apoptosis and results in targeted-therapy resistance, compared to CD133-cells.…”
Section: Notch Signaling and Cscsmentioning
confidence: 99%
“…Findings from xenograft experiments further demonstrated that CD133+ cells are able to retain a higher tumorigenic capacity than their counterpart, thus indicating their tumor-initiating feature. In addition, Notch inhibition by DAPT combined with EGFR inhibitor (AG1478) treatment on EC cells displays ameliorative effects compared to DAPT or AG1478 treatments alone, thus reducing the CD133+ cells viability [71] .…”
Section: Notch Signaling and Cscsmentioning
confidence: 99%
“…RO4929097reduces the chemoresistance and metastasis in CC cells [31]. SiHa) compared with HPV-negative cell line (C-33A).…”
Section: Notch Signaling Pathwaymentioning
confidence: 99%
“…Despite initial therapeutic response, the majority of patients either undergo relapse or succumb to the disease as a result of resistance to chemotherapy [ 15 ]. Chemoresistance is the most important factor that decreases or abrogates the efficacy of chemotherapy in many cancers including advanced cervical cancer, producing an increase in tumor progression, which results in high rates of cancer-related deaths [ 16 , 17 ]. Many factors contribute to chemoresistance, including but not limited to, alterations in DNA damage and repair capacity, and overexpression of ATP-binding cassette (ABC) transporters, notably the ABCB1 transporter [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%